1984
DOI: 10.1071/pp9840319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Nutrition and Light Upon the Concentrations of Alanine in Leaves of C4 Plants

Abstract: The concentration of alanine in the leaves of representatives of each of the three types of C4 plants was found to be consistently greater in sodium-deficient than in sodium-sufficient plants. The sodium treatment, however, did not affect the alanine concentration in the leaves of tomato, a C3 plant or in the roots of Amaranthus tricolor, a C4 plant. The alanine concentration of leaves of A. tricolor decreased rapidly upon the addition of sodium to cultures of sodium-deficient plants. The concentration of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
3
4
0
Order By: Relevance
“…Analysis of stomata1 conductance (Boag 1981) and carbonic anhydrase (Brownell e t al. 1991) support the hypothesis of Nable and Brownell (1984) that the regeneration of the primary C 0 2 acceptor, PEP, in the mesophyll chloroplasts limits photosynthesis in sodiumdeficient plants.…”
Section: Introductionsupporting
confidence: 63%
“…Analysis of stomata1 conductance (Boag 1981) and carbonic anhydrase (Brownell e t al. 1991) support the hypothesis of Nable and Brownell (1984) that the regeneration of the primary C 0 2 acceptor, PEP, in the mesophyll chloroplasts limits photosynthesis in sodiumdeficient plants.…”
Section: Introductionsupporting
confidence: 63%
“…The three containers with plants were placed in an air-tight box made of Plexiglas (36 L) and the box was set in the environment chamber. The air was labeled with 8 IuCi '4CO2, which was prepared from 20 mg Ba'4CO3 and 10 mL 60% HC104. The initial CO2 concentration was about 400 ppm.…”
Section: Photosynthesismentioning
confidence: 99%
“…Grof et al (5) reported that organization of mesophyll chloroplasts ofKochia childsii and A. tricolor plants was a sodiumdependent process. In previous papers (1 [1][2][3][4][5][6][7][8][9][10][11][12][13], we have reported that sodium affects growth ofA. tricolor plants through its stimulation of nitrate uptake and reduction.…”
mentioning
confidence: 99%
“…Leaves of sodium-deficient C, plants have been shown to have increased concentrations of alanine (Nable and Brownell 1984;Grof et al 1986a) and pyruvate (Johnston et al 1988) and decreased concentration of PEP* (Johnston et al 1988). This suggests a possible block in the regeneration of PEP from pyruvate in the mesophyll chloroplasts in sodium-deficient plants.…”
Section: Introductionmentioning
confidence: 99%